Dampak korupsi sebagai penghambat ekonomi dan investasi di Indonesia - Maghfiroh, Maya Abidatun (Maliki Interdisciplinary Journal, 2026)
Corruption in Indonesia has become a systemic problem that cripples the economic structure and significantly impedes capital flows. This study aims to analyze the mechanisms of corruption as a structural obstacle to achieving sustainable economic growth and a conducive investment climate. Using a qualitative descriptive method based on literature, it was found that corruption functions as a "hidden tax" that fuels a high-cost economy. This practice undermines fair market competition, distorts the allocation of public resources, and erodes foreign direct investment confidence. Furthermore, legal uncertainty resulting from bureaucratic bribery weakens national competitiveness and triggers inefficiencies in strategic infrastructure. This study concludes that strengthening institutional integrity, the rule of law, and accelerating digitalization through e-government are essential prerequisites for eliminating investment barriers. Without radical institutional reform, Indonesia risks falling into the middle-income trap. Therefore, eradicating corruption must be a key pillar of a long-term national economic transformation strategy to ensure stability and global competitiveness.